Control of brucellosis on an infected Murrah buffalo farm with reduced dose of Brucella abortus S19 vaccine administered by conjunctival route in adult animals - CHAND, PURAN; CHHABRA, RAJESH; JALE, ISHWAR SINGH; BANGER, RAJIV; JANGRA, SUBHASH (The Indian Journal of Animal Sciences, 2013)
Brucellosis caused by Brucella abortus is a serious threat to dairy farming particularly when the area is endemicwith no effective vaccination programme. Abortion is the main outcome of brucellosis in pregnant animals with furthercomplication of retention of placenta, reduced milk yield, metritis, temporary or permanent infertility, cost of veterinaryservices, increased inter-calving period and maintenance of unproductive animal. Owing to abortions, a contaminatedenvironment with a high antigenic load of B. abortus is created on the farm in which vaccination of calves alone is notsufficient to control brucellosis. Vaccination of adult animals including calves would be an effective strategy to controlabortions and bring down incidence of the disease. In the present study, attempts were made to control brucellosis on aMurrah buffalo farm where brucellosis entered about 5 years ago, and since then 86 abortions had occurred resultinginto colossal losses. The strategy of testing of all animals, segregation of positive population, and decontamination offarm premises coupled with vaccination with B. abortus S19 vaccine of adult buffaloes as well as calves (4–8 months)was adopted. Adult buffaloes were vaccinated with reduced dose of S19 vaccine by conjunctival route and boosted after4 months while calves were vaccinated by single standard dose of S19 vaccine by subcutaneous route. Only 6.52% (6/92) adult buffaloes became serologically positive after 1 month of conjunctival vaccination, however, these animalsalso became negative after 2 months. The drawback of subcutaneous vaccination of adult animals that they becomeserologically positive with persistent antibody titres interfering in subsequent testing was circumvented by using theconjunctival route of vaccine administration. Abortions in buffaloes were not recorded after vaccination.